In vivo degradation profile of porcine cartilage-derived extracellular matrix powder scaffolds using a non-invasive fluorescence imaging method. Issue 2 (22nd January 2016) - Kim, Hyeon Joo; Lee, Soyeon; Yun, Hee-Woong; Yin, Xiang Yun; Kim, Soon Hee; Choi, Byung Hyune; Kim, Young Jick; Kim, Moon Suk; Min, Byoung-Hyun
Abstract: We present a non-invasive fluorescence method for imaging of scaffold degradation in vivo by quantifying the degradation of porcine cartilage-derived extracellular matrix powder (PCP).Three-dimensional porous scaffolds should be biocompatible and bioresorbable, with a controllable degradation and resorption rate to match tissue growth. However, in vivo scaffold degradation and tissue ingrowth processes are not yet fully understood. Unfortunately, current analysis methods require animal sacrifice and scaffold destruction for the quantification of scaffold degradation and cannot monitor the situation in real time. In this study, Cy3, a fluorescent dye, was used for visualizing PCP and a real-time degradation profile was obtained quantitatively by a non-invasive method using an imaging system in which the reduction in fluorescence intensity depended on PCP scaffold degradation. Real-time PCP scaffold degradation was confirmed through changes in the volume and morphology of the scaffold using micro-computed tomography and microscopy. Our results suggest that extracellular matrix degradation was induced by collagen degradation because of the binding between Cy3 and collagen. This non-invasive real-time monitoring system for scaffold degradation will increase our understanding of in vivo matrix and/or scaffold degradation.